Impact of climate changes on Arizona State precipitation patterns using high-resolution climatic gridded datasets - Hayder H. Kareem; Shahla Abdulqader Nassrullah (Journal of Groundwater Science and Engineering)
Climate change significantly affects environment, ecosystems, communities, and economies. These impacts often result in quick and gradual changes in water resources, environmental conditions, and weather patterns. A geographical study was conducted in Arizona State, USA, to examine monthly precipitation concentration rates over time. This analysis used a high-resolution 0.50×0.50 grid for monthly precipitation data from 1961 to 2022, Provided by the Climatic Research Unit. The study aimed to analyze climatic changes affected the first and last five years of each decade, as well as the entire decade, during the specified period. GIS was used to meet the objectives of this study. Arizona experienced 51–568 mm, 67–560 mm, 63–622 mm, and 52–590 mm of rainfall in the sixth, seventh, eighth, and ninth decades of the second millennium, respectively. Both the first and second five year periods of each decade showed acceptable rainfall amounts despite fluctuations. However, rainfall decreased in the first and second decades of the third millennium. and in the first two years of the third decade. Rainfall amounts dropped to 42–472 mm, 55–469 mm, and 74–498 mm, respectively, indicating a downward trend in precipitation. The central part of the state received the highest rainfall, while the eastern and western regions (spanning north to south) had significantly less. Over the decades of the third millennium, the average annual rainfall every five years was relatively low, showing a declining trend due to severe climate changes, generally ranging between 35 mm and 498 mm. The central regions consistently received more rainfall than the eastern and western outskirts. Arizona is currently experiencing a decrease in rainfall due to climate change, a situation that could deteriorate further. This highlights the need to optimize the use of existing rainfall and explore alternative water sources.